Antibacterial activity tannin-rich fraction from leaves of Anacardium humile - Perácio Rafael Bueno Ferreira; Cíntia Sorandra Oliveira Mendes; Cínthia Gracielly Rodrigues; Juliane Caroline Moura Rocha; Vanessa de Andrade Royo; Henrique Maia Valério; Dario Alves de Oliveira (2012)
In vitro tests conducted with extracts rich in tannins have identified several biological activities of this class of substance. Thus, this paper intends to evaluate the antibacterial activity of tannin-rich fraction obtained from leaf extracts of Anacardium humile A.St.-Hil. Extracts of A. humile leaves in 70% acetone were semi-purified with ethyl acetate and butanol. We quantified the total tannins of the semi-purified fractions, of the crude extract and of aqueous residues and then performed tests of the antibacterial activity of the tannins against Staphylococcus aureus ATCC 6538, Pseudomonas aeruginosa ATCC 27853 and Enterococcus faecalis ATCC 29212. All positive extracts underwent tannin isolation using a Sephadex LH-20 column. The tannins isolated from the samples were quantified and tested for the minimal inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC). The tannins from crude extracts, semi-purifications and residues showed inhibition of S. aureus growth with MIC=500 g mL-1. All tannin fractions showed MIC against all strains and MBC, except against E. faecalis. The tannin fractions from Anacardium humile have antibacterial activity against Staphylococcus aureus, Pseudomononas aeruginosa and Enterococcus faecalis and, therefore, may be promising for future synthesis of new antibacterial agents.